Parallel Genetic Architecture of Parallel Adaptive Radiations in Mimetic Heliconius Butterflies - Kronforst, Marcus R. (Copyright © 2006 by the Genetics Society of America, 2006)
It is unknown whether homologous loci underlie the independent and parallel wing pattern radiations of Heliconius butterflies. By comparing the locations of color patterning genes on linkage maps we show that three loci that act similarly in the two radiations are in similar positions on homologous chromosomes.